PENGEMBANGAN MEDIA PENDIDIKAN SEKSUAL BERBASIS ANDROID “DEAR MOMS” SEBAGAI UPAYA PENGENDALIAN PELECEHAN SEKSUAL PADA ANAK - Bilqia, Biqis (Jurnal Diskursus Pendidikan Sosiologi, 2021)
Sexual abuse of children is a reflection of the importance of children to protect themselves by providing sexual education to children who are guided by their parents. The lack of sexual education provided to children also affects the selection of content that could be accessed by children on social media. Therefore, the purpose of this study is to describe the development of android-based sexual education media as an effort to control sexual abuse in children and to implement android-based sexual education media for the prevention of sexual abuse in children. validation which was analyzed using the the media feasibility formula by Mardapi which in this case resulted in an assessment of 86.36% obtained from media experts and 93.75% from material experts. the percentage of 85.71% is based on the assessment of parents, which means the developed media could and feasible to use where sexual education is an effort to prevent children from being exploited against sexual violence.